EFISIENSI PRODUKSI DAN PROSPEK AGRIBISNIS PEPAYA DI KABUPATEN BOYOLALI - Rhina Uchyani; Wiwit Rahayu; Erlyna Wida R (Universitas Sebelas Maret, 2006)
The objectives of research are to know factors that influence papaya farming production, factors that influence profit of papaya farming, efficiency and prospect agribusiness of papaya farming. The research was carried out of three villages are Mojosongo, Kemiri and Butuh at Mojosongo sub district regency